Analysis of the Application of Inventory Accounting Information Systems - Alodia Salsabila Putri Wijaya; Muhammad Sodik; Endah Puspitosarie (Optima Science, 2024)
The development of the industry that is currently increasing rapidly makes the level of competition even tighter. Companies need to pay attention to several things in the face of competition, one thing that really needs to be considered is inventory for the smooth running of the entire order fulfillment process on CV. Prosperous Business Development. This research was conducted to find out whether the implementation of the inventory accounting information system at the company has been running in accordance with production operational standards or still needs improvement. The results showed that the Accounting Information System at CV. Bina Usaha Sejahtera is still not running optimally because existing production operational standards are not properly implemented by employees.